Lead exposure during childhood and subsequent anthropometry through adolescence in girls. (January 2019) - Deierlein, Andrea L.; Teitelbaum, Susan L.; Windham, Gayle C.; Pinney, Susan M.; Galvez, Maida P.; Caldwell, Kathleen L.; Jarrett, Jeffery M.; Gajek, Ryszard; Kushi, Lawrence H.; Biro, Frank; Wolff, Mary S.; ,
Abstract: Introduction: Cross-sectional studies suggest that postnatal blood lead (PbB) concentrations are negatively associated with child growth. Few studies prospectively examined this association in populations with lower PbB concentrations. We investigated longitudinal associations of childhood PbB concentrations and subsequent anthropometric measurements in a multi-ethnic cohort of girls. Methods: Data were from The Breast Cancer and the Environment Research Program at three sites in the United States (U.S.): New York City, Cincinnati, and San Francisco Bay Area. Girls were enrolled at ages 6–8 years in 2004–2007. Girls with PbB concentrations collected at ≤10 years old (mean 7.8 years, standard deviation (SD) 0.82) and anthropometry collected at ≥3 follow-up visits were included (n = 683). The median PbB concentration was 0.99 μg/d (10th percentile = 0.59 μg/dL and 90th percentile = 2.00 μg/dL) and the geometric mean was 1.03 μg/dL (95% Confidence Interval (CI): 0.99, 1.06). For analyses, PbB concentrations were dichotomized as <1 μg/dL (n = 342) and ≥1 μg/dL (n = 341). Anthropometric measurements of height, body mass index (BMI), waist circumference (WC), and percent body fat (%BF) were collected at enrollment and follow-up visits through 2015. Linear mixed effects regression estimated how PbB concentrations related to changes in girls' measurements from ages 7–14 years. Results: At 7 years, mean difference in height was −2.0 cm (95% CI: −3.0, −1.0) for girls with ≥1 μg/dL versus <1 μg/dL PbB concentrations; differences persisted, but were attenuated, with age to −1.5 cm (95% CI: −2.5, −0.4) at 14 years. Mean differences for BMI, WC, and BF% at 7 years between girls with ≥1 μg/dL versus <1 μg/dL PbB concentrations were −0.7 kg/m 2 (95% CI: −1.2, −0.2), −2.2 cm (95% CI: −3.8, −0.6), and −1.8% (95% CI: −3.2, −0.4), respectively. Overall, these differences generally persisted with advancing age and at 14 years, differences were −0.8 kg/m 2 (95% CI: −1.5, −0.02), −2.9 cm (95% CI: −4.8, −0.9), and −1.7% (95% CI: −3.1, −0.4) for BMI, WC, and BF%, respectively. Conclusions: These findings suggest that higher concentrations of PbB during childhood, even though relatively low by screening standards, may be inversely associated with anthropometric measurements in girls. Highlights: Few studies prospectively examined association of childhood lead and anthropometry. This study included a multi-ethnic US population of girls with low lead concentrations. Anthropometric measurements were taken ≥3 times during follow-up. Lead concentrations ≥1 μg/dL were negatively associated with anthropometry at ages 7–14 years. Future research should include investigation of low blood lead concentrations.